NILAI KESEDERHANAAN DAN NILAI KEDISIPLINAN SEBAGAI LANDASAN KEHIDUPAN MASYARAKAT JEPANG - Sri Sudarsih (KIRYOKU, 2017)
Japanese learn from his defeat in the second world war. The condition made japan hold improvement especially on habits and customs.Willing to learn from her lack and her want themselves into a turning point a change to a better direction.Finally japan known as one of the modern state of and forward since the middle of the 20th century until now.This is accomplished achievement on many reforms the centre of life.The value of simplicity and value of discipline as the basis the lives of the community made Japan experienced its former glory.